PENGEMBANGAN E-BOOK BERBASIS PENDEKATAN SAINTIFIK PADA MATERI SIKLUS HIDUP HEWAN KELAS IV SEKOLAH DASAR - Dwiputri, Sekar; Wahyudiana, Endang; Hasanah, Uswatun (Universitas Nusantara PGRI Kediri, 2022)
This research creates e-book based-scientific on animal life cycle material at 4th grade Elementary School. This type of research is research and development with ADDIE model. The subjects were the fourth grade students of SDN Kebon Baru 09. The data obtained were collected through questionnaires and observation. The respondents in this research were instructional design experts, materials experts, linguists and the fourth grade students. The results showed that the feasibility of e-book based on a scientific approach were